Affirmative action outcomes: evidence from a law school in Brazil - Ribeiro, Ana Carolina Trindade (2017)
The main goal of affirmative action (AA) policies is to give opportunities otherwise nonexistent to minorities and underprivileged students. In this paper, I investigate whether the introduction of a college affirmative action policy enables AA beneficiaries to obtain a career in Law and to catch up with high scoring candidates who did not get admitted due to the policy (i.e., displaced candidates). To do so, I use a new dataset from UERJ admission office, a prominent public university in Rio de Janeiro, which was the first in Brazil to adopt a quota system for both black and public school students. I combine this dataset with the OAB exam passage records, equivalent to the American Bar exam. Preliminary results suggest that the quota policy improves OAB passage rates for beneficiaries. I find that lawyer certification for underprivileged students increases by 51 p.p., even though they underperform by 4.56 p.p when compared to displaced candidates. I also present evidence that displaced candidates do not experience any drop in their OAB exam passage rates due to the policy. Furthermore, I find that public school quota beneficiaries who score close to the admission cutoff present an increase in the probability of passing the OAB exam by up to 52 p.p.